2019
DOI: 10.1145/3306346.3322965
|View full text |Cite
|
Sign up to set email alerts
|

Warp-and-project tomography for rapidly deforming objects

Abstract: Computed tomography has emerged as the method of choice for scanning complex shapes as well as interior structures of stationary objects. Recent progress has also allowed the use of CT for analyzing deforming objects and dynamic phenomena, although the deformations have been constrained to be either slow or periodic motions. In this work we improve the tomographic reconstruction of time-varying geometries undergoing faster, non-periodic deformations. Our method uses a warp-and-project approach that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…A projection image from the 2,600 Re is shown in Figure 5(b). The normalized LII image, and reconstructed slices from our method (Ours) and Zang et al [53] method at 117°are shown respectively in Figure 5(c-e) indicating sharper results with reasonably finer soot structures that can be observed from our method. , where one soot raw image from the video captured by camera 1 is shown.…”
Section: Real World Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…A projection image from the 2,600 Re is shown in Figure 5(b). The normalized LII image, and reconstructed slices from our method (Ours) and Zang et al [53] method at 117°are shown respectively in Figure 5(c-e) indicating sharper results with reasonably finer soot structures that can be observed from our method. , where one soot raw image from the video captured by camera 1 is shown.…”
Section: Real World Resultsmentioning
confidence: 66%
“…The appearance transfer based method (Okabe et al) for fluid modeling proposed by [36] is compared as the third baseline. The last baseline (Zang et al) reconstructs fast deforming object with internal structure by X-ray CT scanner via a so called warp-and-project strategy proposed in [53]. Since the problem we are tackling is highly underdetermined, improved results are achieved for each method by constraining the reconstruction to the visual hull [29] of each data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations